Frame by frame: empowering ESL learners through visual writing - Aris, Haziqah Zulaikha; Hussain, Annur Najiah Hussaini; Shamsuddin, Aizat (Perpustakaan Tun Abdul Razak UiTM Negeri Sembilan, 2025)
This study explores the use of storyboard templates as a visual learning tool to support ESL students in writing the CEFR-aligned PT3 English Essay (Part 1). Storyboarding allows students to visualize, plan, and organize their ideas in sequence, helping them write with greater confidence, creativity, and clarity. Rooted in cognitive and constructivist learning theories, and aligned with the multiliteracies approach, the method promotes student-centered, multimodal engagement. A qualitative research design was employed using semi-structured interviews to investigate students’ perceptions and the impact of storyboard use on their writing process. Thematic analysis of the data revealed three major themes: (1) improved writing skills in terms of structure and fluency, (2) enhanced confidence and time management, and (3) mixed reactions toward the fixed visuals and limited writing space. While many students appreciated the storyboard’s guidance, others expressed a desire for more creative freedom. Nevertheless, most acknowledged its usefulness in supporting idea development and essay planning. Some students even recommended its application in other subjects, such as Malay Language and History. This research highlights the pedagogical value of visual tools in language instruction and suggests that storyboarding offers a practical, accessible shift from traditional text-heavy approaches to a more engaging, student-focused writing model.